STUDI TINGKAT STRES SERTA ANALISA HUBUNGAN KEBERADAAN BREEDING PLACES, PRAKTIK 3M, PRAKTIK MEMBUANG SAMPAH TERHADAP KASUS DEMAM BERDARAH DENGUE DI KOTA SEMARANG - Raynaldi Raynaldi; Nur Endah Wahyuningsih; Resa Ana Dina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Generally Dengue is transmitted by the bite of Aedes mosquito that was infected by dengue virus to humans in the form of the disease known as dengue fever (DF), Dengue Hemorrhagic Fever (DHF) and Dengue Shock Syndrome (DSS), Semarang since 2009 DHF had happened endemic throughout territory. This study aimed to describe the stress level and analyzed the factors associated with dengue cases in the city of Semarang. This research is analytic survey with case-control study design. The research sample comprised 82 respondents (productive age, 15-59 years) taken by total population being inclusion and exclusion criteria are divided into 41 respondents and 41 respondents cases where control is taken control group based on criteria matched to the case group. Samples were taken using the criteria of inclusion and exclusion of patients who had met at the hospital for approval following the research. Data were analyzed using descriptive analysis and correlation analysis with chi-square test at the significant level of 5% (0.05). Results of the analysis showed no difference in the level of stress in the case and control groups. Results of the study showed no association of variables where breeding places (TPA grocery p = 0.627, not grocery p = 0.500, natural p = 0.305), the practice of 3M (p = 0.070) and the practice of taking out the trash (p = 0.635) with dengue cases.